Authentic leadership and motivation as moderators of the organizational politics–knowledge sharing relationship: A test amidst crisis - Arias Rodriguez, Indira [UNESP]; Muniz, Jorge [UNESP]; Munyon, Timothy P (SAGE Publications, 2024)
Organizational politics are recognized as a ubiquitous and negative threat to knowledge sharing in organizations, yet less research has examined the boundary conditions that affect this relationship, particularly in interdependent manufacturing contexts. This article aims to explore how authentic leadership, intrinsic motivation, and prosocial motivation bound the effects of organizational politics on the knowledge sharing activities of individuals and workgroups in the shop floor of the Brazilian automotive consortium during a political and economic crisis context (2015–2017). This crisis context was marked by presidential impeachment, high inflation, economic instability, and massive plant layoffs. We sampled 144 shop floor workers using a questionnaire-based survey and established scales, and employed multivariate regression analyses to test our hypotheses. Contrary to expectations, we found that organizational politics increase, rather than decrease, knowledge sharing of individuals and groups. Moderation analyses suggest that worker intrinsic motivation and prosocial motivation significantly moderate the positive relationships between organizational politics and knowledge sharing of individuals and groups, while authentic leadership had no significant effect on this relationship. JEL CLASSIFICATION: D2: Production and Organizations.
Keywords: authentic leadership; intrinsic motivation; knowledge sharing; Organizational politics; prosocial motivation